2022
DOI: 10.3390/v14030607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Biostimulants Added with Zeolite on Zucchini Squash Plants Infected by Tomato Leaf Curl New Delhi Virus

Abstract: The use of organic substances in integrated pest management can contribute to human- and environment-safe crop production. In the present work, a combination of organic biostimulants (Fullcrhum Alert and BioVeg 500) and an inorganic corroborant (Clinogold, zeolite) was tested for the effects on the plant response to the quarantine pest tomato leaf curl New Delhi virus (ToLCNDV). Biostimulants were applied to healthy and infected greenhouse-grown zucchini plants, and the vegetative parameters and viral titer we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Their findings revealed overall similar metabolic changes in the leaves under viral stress, which is consistent with our results. Various metabolite markers have been identified in different studies that investigated the alteration of plant metabolome under geminivirus infection Donati et al, 2022) . Additionally, a similar set of 1H NMR peaks for legume plant metabolome has been previously reported in several studies (Chen et al, 2019;Bueno and Lopes, 2020;Villa-ruano et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Their findings revealed overall similar metabolic changes in the leaves under viral stress, which is consistent with our results. Various metabolite markers have been identified in different studies that investigated the alteration of plant metabolome under geminivirus infection Donati et al, 2022) . Additionally, a similar set of 1H NMR peaks for legume plant metabolome has been previously reported in several studies (Chen et al, 2019;Bueno and Lopes, 2020;Villa-ruano et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Natural plant bio-stimulants can be used as environmentally friendly alternatives to agricultural chemicals. A recent study reported that such bio-stimulants (e.g., Fullcrhum Alert and BioVeg 500) affected the fitness of zucchini plants against ToCLNDV (Donati et al 2022 ). Essential oils (EOs) and hydrosols (HS) derived from natural plant products have also gained attention.…”
Section: Disease Managementmentioning
confidence: 99%
“…Zeolite foliar treatments showed interesting results on grapevines for containing fungal diseases [ 17 ], on apple trees [ 18 ], and olive trees in conditions of water stress [ 19 ]. A combination of organic biostimulants with an inorganic corroborant (zeolite) was also tested for the plant response to the quarantine pest tomato leaf curl New Delhi virus [ 20 ].…”
Section: Introductionmentioning
confidence: 99%